2005
DOI: 10.1016/j.jnt.2004.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Pesenti–Szpiro inequality for optimal elliptic curves

Abstract: We study Pesenti-Szpiro inequality in the case of elliptic curves over F q (t) which occur as subvarieties of Jacobian varieties of Drinfeld modular curves. In general, we obtain an upperbound on the degrees of minimal discriminants of such elliptic curves in terms of the degrees of their conductors and q. In the special case when the level is prime, we bound the degrees of discriminants only in terms of the degrees of conductors. As a preliminary step in the proof of this latter result we generalize a constru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…D] (modulo the assumptions we made). Using the argument in the proof of [17,Thm.6.4], one can show that deg ℘ is bounded from below by α · N (n E )/(deg n) 2 , where α is a constant depending only on q, g and deg ∞. Thus, log(deg ℘) deg n E and the bound in the theorem is essentially the best possible.…”
Section: Theorem 12 With Previous Notation and Assumptions We Havementioning
confidence: 97%
See 1 more Smart Citation
“…D] (modulo the assumptions we made). Using the argument in the proof of [17,Thm.6.4], one can show that deg ℘ is bounded from below by α · N (n E )/(deg n) 2 , where α is a constant depending only on q, g and deg ∞. Thus, log(deg ℘) deg n E and the bound in the theorem is essentially the best possible.…”
Section: Theorem 12 With Previous Notation and Assumptions We Havementioning
confidence: 97%
“…We only indicate the main steps which go into the proof of this theorem and refer to [17,Thm. A.4] for the details.…”
mentioning
confidence: 99%
“…Although this hypothesis is frequently made (sometimes implicitly) in the literature (see for example [Papikian 2005;Rück and Tipp 2000]), it is actually false. One of the aims of this paper is to exhibit many cases when m(E) is not zero.…”
Section: Referencesmentioning
confidence: 99%
“…More precisely, they are obtained from finitely many curves by repeated application of the Frobenius isogeny. Papikian [Pa1,Pa2] has shown that in certain situations the strong Weil curve is not the Frobenius of another curve over F q (T ), but from examples it is known that this is not a general phenomenon.…”
mentioning
confidence: 99%